Majas Perbandingan pada Novel Ingkar Karya Boy Candra (Kajian Stilistika) - Sulistiya, Febrianti; Prameswari, Jatut Yoga; Anam, Ahmad Khoiril; Purnama, Yogi; Mulyani, Sri (MARDIBASA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2022)
The purpose of this study is to interpret the types of comparative compounds in the novel Ingkar by Boy Candra. This research uses qualitative description research methods. The study as a whole utilizes interpretation in presenting data in descriptive form. The research methods in this study use documentation techniques. The instrument in this study is the researcher himself as a human instrument. The results of comparative compound findings in the novel Ingkar by Boy Candra found as many as 250 data with comparative comparison of parables as many as 68 sentences (27.2%), metaphorical majas as many as 27 sentences (10.8%), majas personification as many as 62 sentences (24.8%), majas depersonification as many as 40 sentences (16%), allegory majas as much as 12 sentences (4.8%), antithesis majas as many as 22 sentences (8.8%), majas pleonasme and tautology as many as 11 sentences (4.4%), majas perifrasis as many as 3 sentences (1.2%), and majas anticipation as many as 5 sentences (2%). Majas comparison is dominant in the novel Ingkar by Boy Candra, which is a comparison of parable categories as much as 68 sentences with a percentage of 27.2%.